Additive manufacturing of high tensile strength steel for offshore & marine 3D complex joint applications - Wu, Wenjin (Nanyang Technological University, 2021)
Additive manufacturing (AM) technology can potentially disrupt offshore and marine industry by effectively reducing manufacturing processes and leadtime, and enabling new product designs. A review of existing literature has revealed limited knowledge in using AM to process shipbuilding materials, which can otherwise enhance existing shipbuilding manufacturing workflow. This has led to the research motivation to establish the technical feasibility of using selective laser melting (SLM) to process ASTM A131 EH36 shipbuilding steel. SLM process is a widely understood AM technology that has been used extensively to process other type of steels, for example stainless steel 316L. EH36 belongs to a class of high tensile low alloy steel which has traditionally been processed through casting. However, knowledge on using lasers to process EH36 is largely unknown, especially in AM applications. Using SLM to process EH36 is novel and will solve the problem of lack of knowledge in this field. The study thus aims to further the understanding of the mechanical properties and microstructure of SLM processed EH36. A preliminary investigation was first carried out to establish the technical feasibility of using SLM to process EH36. The process parameters obtained were then used to further the investigations. Heat treatment process was applied as a possible post processing technique. Mechanical testing was carried out to characterise its mechanical properties. The fracture surfaces and microstructures were then studied to characterise the material. The results showed that EH36 can be processed using SLM without any visible cracks. The mechanical properties of as built SLM processed EH36 exhibit very high tensile strength, but low ductility. The ductility can be improved through tempering heat treatment process, but at the partial sacrifice of tensile strength. Fractography analysis also affirmed the lack of ductility in the SLM processed EH36 samples. Finally, the microstructure showed that fine grain size and martensitic microstructure were the primary drivers behind its high tensile strength. Tempered samples experience grain coarsening and phase transformation to a mainly ferritic structure, which led to recovery in its ductility but a decrease in the tensile strength. A scaled model was fabricated to validate the results from the microstructure studies, and the findings indicate similar microstructures formed. This demonstrates the repeatability of the developed process parameters on fabrication of complex joints. The study contributes to the scientific knowledge with regard to material and mechanical property characterisation of SLM processed EH36. The findings from the fractography and microstructural analysis will contribute towards building the knowledge and facilitate future work on AM of EH36.